PENGAWASAN CAMAT DALAM PELAKSANAAN ANGGARAN PENDAPATAN DANA BELANJA DESA (SUATU STUDI DI KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA) - LIJU, SUWINLI JUHANDI; DENGO, SALMIN; LONDA, VERY (Sam Ratulangi University, 2017)
Abstract: this research is moving on from a phenomenon still the existence of weaknesses in the implementation of thesupervision of the head toward the implementation of APB-village, so that the objective of the research was to find outhow the supervision of the head in the implementation of APB-village Subdistricts Of North Minahasa Regency Kauditan.This research uses a quantitative approach method. The informant is head of research/Secretary of the district, the villagechief, caretaker and administrator BPD LPM, in total as many as nine informants. Data collection using the guidelinesof the interview, while the analysis techniques used are interactive model analysis from Miles and Huberman.The results showed a direct Supervision in the implementation of APB-head of the village has not been implementedoptimall by performing the construction directly against the Government in the preparation of APB village-Village;perform evaluation of the draft local regulations about APB villages before submitted to the Governors; monitoring directlyinto villages against the implementation of APB-Village; and down directly to the village if there is information orreports about the discrepancies or irregularities. Indirect supervision towards the implementation of APB-well done by theVillage Head by requesting written reports periodically every quarter on the development and realisatio implementation ofAPB-Village; ask for oral explanations and reports to the head of the village on the implementation of APB-coordinationmeeting at the level of Village sub district; and do report evaluation of the realization of the APB villages eachsemester that will be presented to the Governors.Keywords: Supervision, Camat, Budget.